Impact of a Community Gardening Project on Vegetable Intake, Food Security and Family Relationships: A Community-based Participatory Research Study - Carney, Patricia A. (2012)
PURPOSE: To describe the impact of a community gardening project on vegetable intake, food security and family relationships. METHODS: This community-based participatory research project used popular education techniques to support and educate Hispanic farm worker families in planting and maintaining organic gardens. Measures included a pre- post gardening survey, key informant interviews and observations made at community-based gardening meetings to assess food security, safety and family relationships. RESULTS: Thirty-eight families enrolled in the study during the pre-garden time period, and four more families enrolled in the study during the post-garden period, for a total of 42 families enrolled in the 2009 gardening season. Of the families enrolled during the pre-gardening time period there were 163 household members. The mean age of the interviewee was 44.0, ranging from 21 to 78 years of age. The median number of occupants in a household was 4.0 (range: 2 to 8), Frequency of adult vegetable intake of “Several time a day” increased from 18.2% to 84.8%, (p < 0.001) and frequency of children’s vegetable intake of “Several time a day” increased from 24.0% to 64.0%, (p = 0.003). Before the gardening season, the sum of the frequencies of “Sometimes” and “Frequently” worrying in the past month that food would run out before money was available to buy more was 31.2% and the sum of these frequencies dropped to 3.1% during the post garden period, (p = 0.006). The frequency of skipping meals due to lack of money was not statistically significantly different before and after the gardening season for either adults or children. Analysis of text responses and key informant interviews revealed that physical and mental health benefits were reported as well as economic and family health benefits from the gardening study, primarily because the families often worked in their gardens together. CONCLUSIONS: A community gardening program can reduce food insecurity, improve dietary intake and strengthen family relationships.